G241 Incidence and outcomes of infants with congenital diaphragmatic hernia associated with cardiovascular malformation: a 10 years retrospective study. (12th March 2018) - Newman, T; Weidenmuller, M; Singh, Y
Abstract : Background: Congenital diaphragmatic hernia (CDH) occurs in 1.7–5.7/10, 000 live births and is associated with significant neonatal mortality. It is reported to be associated with congenital cardiovascular malformations (CCM) in up to 10.6% cases, an association which significantly increases mortality. Aims: To study the incidence and outcomes of infants with CDH associated with significant CCM in a UK tertiary neonatal referral centre. Methods: PA retrospective observational study involved all infants diagnosed with CDH and admitted to our maternity hospital between Jan 2007-Dec 2016. Data was collected from electronic patient records. Results: A total of 52 infants diagnosed with CDH were identified. median gestation was 38 weeks (IQR: 36–39 weeks) and average birth weight was 2820 grams (IQR: 2200–3260 grams). 10 infants (19%) had associated CCM as shown in table 1. PFO and PDA were excluded as thought normal findings in this population. Overall survival in our cohort was 79% (41/52) whilst 11 patients (21%) died during infancy. 4 of the 10 infants (40%) with CDH and CCM died whilst mortality was 17% in infants without such association. Pre-operative mortality was higher in infants with CCM, 30% Vs 12% in infants without CCM. Half of the infants with CCM needed transfer to specialist ECMO cardiac centres. Only 2 of the 42 infants without CCM needed transfer for ECMO. Conclusion: In our cohort, there was an increased incidence of significant CCM concomitant with CDH than previously reported. Moreover, there was lower incidence of mortality in our cohort. Associated CCM, however, still greatly increased the risk of requiring additional specialist care and increased mortality rates as compared to CDH alone.